Root-Knot Nematode Management in Caladium - Mengyi Gu; Johan Desaeger (EDIS)
Florida leads the commercial production of caladiums, a popular ornamental. In Florida, root-knot, sting, and stubby root nematodes are found in caladium fields. Root-knot nematodes are considered the most important of all pests in caladiums that are grown in sand. This publication will help caladium growers understand what plant-parasitic nematodes are and current nematode management strategies for the caladium industry.